The impact of urbanization on poverty reduction: An evidence from Vietnam - Nguyen Minh Ha; Nguyen Dang Le; Trung-Kien Pham (Cogent Economics & Finance, 2021)
Poverty is a global socio-economic phenomenon. It is always a problem in all countries include developing countries and developed countries. In Vietnam, the poverty rate has been decreasing while the urbanization has happened rapidly over the past 20 years. Handling the dual problems of urbanization and poverty is important to be able to attain sustainable development. Therefore, this study is to analyze the impact of urbanization on poverty reduction in Vietnam. Using Driscoll and Kraay's method and D-GMM method to estimate the provinces' panel data in the period 2006-2016, we confirm that there exists a U-shape relationship between the level of urbanization and the poverty level in Vietnam. Moreover, the estimated thresholds of urbanization from the perspective of poverty reduction are 40.19% and 43.68% in the static and dynamic model, respectively. In addition, our results exhibit that the gross regional domestic product, human capital, and agricultural value have the effect of reducing poverty, but government spending and export value increases the poverty rate in Vietnam. The paper has relevant implications for policymakers.
Keywords: 330; poverty reduction; urbanization